The Role of Self-Directed Learning in Mediating the Influence of Teaching Enthusiasm on Professional Identity - Hanifah Tria Intan Jelita; Muhammad Fahmi Johan Syah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to explore the role of Self-Directed Learning (SDL) in mediating the influence of Teaching Enthusiasme (TE) on Professional Identity (PI) among students of the Teacher Professional Education Program (PPG) in Indonesia. Using quantitative survey methods and path analysis to analyze the data, this study involved 170 respondents consisting of Professional Education Program (PPG) students at the Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta. The results showed that SDL functions as a critical full mediator between Teaching Enthusiasm and Professional Identity formation. SDL allows students to manage their learning process independently, which in turn increases their engagement in learning and strengthens a professional identity that is relevant to current educational demands. A positive learning environment, intrinsic motivation, and support from mentors were found to contribute significantly to fostering SDL as well as the development of Professional Identity. This study highlights the importance of Teaching Enthusiasm and SDL in shaping professional and adaptive educators, who are able to meet the ever-evolving needs of education. These findings are in line with previous theories that state that SDL not only improves students' academic abilities but also strengthens their character and professional attitudes. Thus, the development of SDL should be a primary focus in teacher education curriculum, so that prospective educators can be better prepared to face challenges in the dynamic world of education. This study provides valuable insights for the development of teacher education programs in Indonesia, and emphasizes the need for SDL integration in learning practices to produce high-quality educators.